Bullying victimization experiences among middle and high school adolescents: Traditional bullying, discriminatory harassment, and cybervictimization. (18th December 2017) - Salmon, Samantha; Turner, Sarah; Taillieu, Tamara; Fortier, Janique; Afifi, Tracie O.
ABSTRACT: The objectives of the current study were to estimate the prevalence of nine types of bullying victimization among adolescents in Grades 7 to 12, and examine how these experiences vary according to gender and school grade. Data were drawn from the Manitoba Youth Health Survey. The sample size was N = 64 174 and included boys and girls from Grades 7 to 12. Nine types of bullying victimization were assessed. Gender and grade differences were noted with girls being more to likely than boys to report six types of victimization. The odds of bullying victimization were higher in Grades 8 to 12 compared to Grade 7. Effective anti‐bullying intervention strategies need to address a range of victimization types and should consider gender and school grade. Interventions should start before Grade 7 and continue until the end of Grade 12.